Pilot Study of the Effect of Plant‐Based Enteral Nutrition on the Gut Microbiota in Chronically Ill Tube‐Fed Children. Issue 7 (15th January 2019) - McClanahan, Danielle; Yeh, Andrew; Firek, Brian; Zettle, Stacey; Rogers, Matthew; Cheek, Richard; Nguyen, Michelle V. L.; Gayer, Christopher P.; Wendell, Stacy G.; Mullett, Steven J.; Morowitz, Michael J.
Abstract: Background: Dietary intake sharply impacts the structure and function of the gut microbiota, which is important for childhood health. However, little is known about the microbiota of children who cannot eat by mouth. Standard enteral formulas for supplemental nutrition are low in fiber and high in processed sugars and are commonly associated with gastrointestinal side effects. In this pilot study, we examined the effects of plant‐based enteral nutrition (PBEN) upon the gut bacteria of chronically ill children. Methods: Ten children (median age 3.5 years, age range 2–8 years) dependent upon conventional enteral formula were transitioned to PBEN for 2 months. Microbial diversity within fecal samples collected before and after PBEN was assessed by 16S ribosomal RNA gene sequence analysis and was compared with rectal swabs from healthy children. Fecal short‐chain fatty acids and bile acids were measured in parallel. Results: Relative to control samples, fecal samples from study subjects were depleted of commensals (eg, Faecalibacterium ) and enriched with pathogens (eg, Enterococcus) . Postintervention samples from study subjects were more similar to healthy controls. Most subjects experienced PBEN‐induced alterations in the gut microbiota, but these changes varied significantly across individuals. Clinical diaries indicated that PBEN was well tolerated, with improvement in symptoms noted in several subjects. Conclusion: Results from this pilot study suggest that PBEN is well tolerated and could improve the health of the microbiota in chronically ill children. This trial provides a rationale for systematic evaluation of PBEN in clinical trials of children who require supplemental nutrition.